EXPLORING ENGLISH LANGUAGE LEARNING STRATEGIES: INSIGHT FROM TIKTOK’S ENGLISH ON THE STREET INTERVIEWS - Fisma Fisma; Rahmat J; Alfrida Dwi Putri (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This study explores the English language learning strategies employed by individuals, drawing insights from spontaneous interviews featured on TikTok’s English on the Street channel. Drawing on Oxford's (1990) taxonomy of language learning strategies, the research aims to explore English language learning strategies as revealed through TikTok’s “English on the Street” interviews. Employing a qualitative descriptive method, the study analyzed 83 publicly available street interview videos using thematic analysis based on Braun, & Clarke (2006). Unlike previous research that has predominantly relied on structured surveys in formal classroom contexts, this study captures how learners naturally express and demonstrate their strategies in real life digital interactions. The findings revealed a diverse use of strategies, with cognitive, social, and metacognitive strategies being the most frequently reported. Participants indicated learning English through media exposure, social interaction, self-directed practices, and to a lesser extent, memory and affective strategies. These results highlight the effectiveness of informal, learner-driven approaches and emphasize the relevance of digital platforms in supporting English learning. Practical implications suggest integrating similar strategies in formal education, while future research is encouraged to investigate underreported strategies such as affective and compensation strategies using more in-depth interviews.